Descortesia linguística: ameaça à imagem nos debates presidenciais brasileiros de 1989 e de 2014 - Andrade, Mariana Santos de (2017)
Political discourse is often marked by clashes between the candidates for an election, who try to establish a self-image (face) that matches society expectations. Considering the controversies among politicians, it is possible that the speech given by them is marked by specific strategies aimed at maintaining their faces and at attacking their opponents’ faces, in order to obtain votes. This research analyses two presidential debates from the perspective of impoliteness studies. The central research problem can be reflected through two questions: a) How is the manifestation of impoliteness, considering the acts that threat the face, in the Brazilian presidential debates of 1989 and 2014? b) In view of the analysis, were there changes in the use of impolite strategies in different temporal divisions in the use of the Brazilian Portuguese? Based on these questions, we developed hypotheses that will be analyzed to guide the writing of this research: a) the political debate is a controversial interaction. Thus, it is necessary that the candidates remain constantly vigilant to preserve their faces, given the goal of winning votes; b) the communication process is guided by linguistic, cultural, ideological and social factors. As part of a complex that involves language and communicative practices of action, we note generally present in linguistic acts strategies needed to install and maintain harmony. However, there may be certain types of interaction in which impoliteness is the rule; c) impoliteness strategies may change over time. In light of the central problem and hypotheses, we intend to analyze the debates a perspective established in Pragmatics, based on the theoretical assumptions proposed by Bravo (1999, 2003, 2004a, 2004b), Blas Arroyo (2001, 2011) and Silva (2013).